Moving towards the replacement of the nih test - Morlot, F. G.; Chabaud-Riou, M.; Chapsal, J. M. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Potency testing of inactivated rabies vaccines is traditionally performed by an intracerebral (IC) challenge method on mice. The method was originally developed by the National Institutes of Health (NIH) in the 1950s for potency testing of inactivated rabies vaccines for human use. The NIH test is widely recognized and is currently required by the World Health Organization (WHO) and Pharmacopoeias for rabies vaccines release. Nevertheless, the NIH challenge method presents a number of limitation and issues:• As a biological test the NIH method is highly variable, making this test inappropriate for batch-to-batch consistency analysis.• A large number of mice is required.• This test is time consuming and labor intensive for both the manufacturer and the authorities that release the batches. For all these reasons, regulators, experts and manufacturers are seeking an alternative method to the existing NIH test that guarantees the potency of the rabies vaccine to be administered for pre or post exposure vaccination. A recent international workshop of the NICEATM and ICCVAM was held in Ames, Iowa, USA on October 11-13th, 2011 on “Alternative Methods for Human and Veterinary Rabies Vaccine Testing” with particular focus on Rabies Vaccine Potency Testing. The main conclusions of this workshop were as follows:• For inactivated veterinary rabies vaccines, the Serum Neutralization Test (SNT) serological method described in the Ph. Eur. Monograph 0451, should be immediately considered for product specific validation by vaccine manufacturers for both adjuvanted and non adjuvanted vaccines. • As human rabies vaccines in some regions (e.g., U.S. and EU) are simpler products (non-adjuvanted, monovalent), manufacturers are encouraged to develop and implement an in vitro antigen quantification method to replace the mouse challenge test. In vitro antigen quantification methods currently used by rabies vaccine manufacturers as in-process tests include ELISA and Single Radial Immunodiffusion (SRID) Test.• Final product in vitro methods will require identification and use of appropriate reagents (e.g. monoclonal antibody) with specificity for the neutralizing epitope of the virus-associated trimeric form of glycoprotein G.• Validation of in vitro replacement tests will need to include identification of sub-potent lots. For validating in vitro methods for potency testing of human rabies vaccines, it may be necessary to compare in vitro results to adequate serological titers in humans. In the context of the Purified Vero Rabies Vaccine next generation (PVRV-NG) development, Sanofi Pasteur has set up an inhouse ELISA test answering the need for an alternative method to the NIH potency test. The description of the corresponding ELISA method for rabies glycoprotein G quantification and the data supporting the alternative test, together with the proposed global strategy for implementing this ELISA test in replacement of the NIH test, will be presented.